Human trafficking among Bangladeshi workers in Malaysia: unveiling the impact on health security - Zarina Othman,; Norliza Dolhan,; Atika Shafinaz Nazri, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article is designed to investigate the effects of trafficking and its multiple types on health security. We contend that human trafficking significantly impacts victims’ health, both mentally and physically, which ultimately affects social life, ability to work, mobility, or migration status. We successfully interviewed several male Bangladeshi trafficking victims working in Malaysia, highlighting their feelings when subjected to situations of abuse, confinement, unpaid wages, restricted freedom of movement following the confiscation of identity documents, and coerced overwork without sufficient rest periods. We underscore how health security can impact other aspects, potentially leading to death, perpetuating poverty and economic vulnerability cycles, and affecting the local community. In addition, the neglect of health security among trafficking victims constitutes a violation of their human rights. Addressing these issues necessitates a comprehensive approach that upholds the rights and dignity of all individuals, irrespective of their circumstances. Therefore, we advocate that Malaysia prioritize the current and post-trafficking conditions of victims by establishing a dedicated agency to monitor their health status. It is essential to ensure that Bangladeshi victims, before repatriation to their home country, are fully recovered, can lead fulfilling lives, and are resilient in seeking other job opportunities.